Sirtuin 3 regulates Foxo3a-mediated antioxidant pathway in microglia. (17th December 2015) - Rangarajan, P.; Karthikeyan, A.; Lu, J.; Ling, E.-A.; Dheen, S.T.
Highlights: Sirtuin 3 (Sirt3) is developmentally regulated in microglia in the rat brain. Sirt3 expression is induced in activated microglia in vitro and in vivo . Sirt3 induces antioxidants through nuclear translocation of Foxo3a, in microglia. Abstract: Microglia are the prime cellular sources of reactive oxygen species (ROS) in the central nervous system (CNS). Chronic activation of microglia has been linked to aging-associated neurodegenerative diseases such as Alzheimer's disease (AD) and Parkinson's disease (PD) since they produce excessive amounts of ROS for a prolonged duration leading to oxidative stress. The present study was aimed at investigating the expression and role of Sirtuin 3 (Sirt3), a protein deacetylase which is implicated in regulating cellular ROS levels. It has been shown that Sirt3 reduces cellular ROS levels by deacetylating forkhead box O 3a (Foxo3a), a transcription factor which transactivates antioxidant genes, catalase (Cat) and manganese superoxide dismutase (mnSod). In the present study, Sirt3 immunoreactivity was localized in the ameboid microglial cells distributed in the corpus callosum (CC) of the early postnatal rat brain and diminished in the ramified microglial cells in the CC of the adult rat brain. A marked induction of Sirt3 expression was seen in lipopolysaccharide (LPS)-activated microglia in vivo and in vitro as well as in adult rat brains subjected to traumatic brain injury (TBI). Knockdown of Sirt3 in microglia led to an increase in the cellular and mitochondrial ROS and decrease in the expression of antioxidant, mnSod which is indicative of the function of Sirt3 in ROS regulation in microglia. Conversely, Sirt3 overexpression led to increase in the expression of antioxidants Cat and mnSod. Further, increase in the expression and nuclear translocation of Foxo3a was observed following Sirt3 overexpression, suggesting that Sirt3 regulates ROS by inducing the expression of antioxidants via activation of Foxo3a. The above results point to an antioxidant defense mechanism presented by Sirt3 through the activation of Foxo3a, in microglia.